Feminist pedagogy, body image, and the dance technique class. Issue 2 (3rd May 2016) - Barr, Sherrie; Oliver, Wendy
Abstract: This paper investigates the evolution of feminist consciousness in dance technique class as related to body image, the myth of the perfect body, and the development of feminist pedagogy. Western concert dance forms have often been taught in a manner where imitating the teacher is primary in the learning process. In this traditional scenario, teachers serve as role models and students strive to emulate their teacher's performance as closely as possible. The authors provide possibilities for broadening such an approach through examining characteristics of feminist pedagogy. The reframing of teaching through a feminist lens reveals options for technique class teaching–learning paradigms to better support student learning in a fully engaged manner.